Baseline red blood cell distribution width predicts long-term glycemic remission in patients with type 2 diabetes. (September 2017) - Xu, Lijuan; Wang, Liangjiao; Huang, Xinwei; Liu, Liehua; Ke, Weijian; He, Xiaoying; Huang, Zhimin; Liu, Juan; Wan, Xuesi; Cao, Xiaopei; Li, Yanbing
Highlights: Low baseline red blood cell distribution widths indicate long-term glucose controls. A faster normalization of glucose during intensive insulin therapy is correlated with a long-term euglycemia. A lower fasting glucose after intensive insulin therapy is associated with a long-term euglycemia. Abstract: Aims: We explored whether red blood cell distribution width (RDW), a routinely checked item of complete blood cell counts, was an indicator of long-term euglycemia remission in patients with type 2 diabetes after short-term continuous subcutaneous insulin infusion (CSII). Methods: We analyzed the original data of patients enrolled in three randomized control trials from 2002 to 2014. CSII was administered to drug-naїve patients with newly diagnosed type 2 diabetes to achieve and maintain euglycemia for 2 weeks. Results: A total of 185 patients were involved and 98 patients (52.97%) who achieved and maintained euglycemia for at least 12 months were classified as the remission group, and the others as the non-remission group. Patients in remission group had a relatively lower value for baseline RDW (38.82 ± 2.76 vs 39.89 ± 2.78 fL, p  = 0.017) compared with those in non-remission group. A graded decrease of remission rate (67.50%, 55.00%, 53.66% and 30.77% for Quartile 1 to Quartile 4 respectively, P  < 0.05) was observed with the increasing of RDWs. The risk of hyperglycemic relapse was significantly increased for those in the highest quartile compared with the lowest (hazard ratio = 2.68; 95% CI, 1.38–5.22). Those who achieved euglycemia within 7 days or obtained a better fasting glucose after therapy had preferable remission rates. Conclusions: Patients with lower baseline RDWs are more likely to maintain a one-year euglycemia remission after short-term CSII. A faster normalization of glucose during treatment and a lower fasting glucose after therapy are correlated with a long-term glucose control.